A Bibliometric analysis of multicultural education in international and Indonesian contexts using Vosviewer - Donna Sampaleng (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The research aims to analyze and describe the theme of multicultural education more comprehensively and in-depth. The method in this study uses a bibliometric analysis approach. Data is sourced from the Scopus publication database. The data search on title-abs-key uses “multicultural education” with limited articles and reviews. Publication years between 2013 -2022 or the last ten years. Data analysis using VOSviewer software. The results of this study show that in the international and Indonesian contexts, the theme of multicultural education has received significant attention and will continue to grow along with the needs and advances of science and technology. In this theme, the United States has the most immense contribution at the international level, and Indonesia contributes the most in South East Asia. In the future, the theme of multicultural education will continue to evolve, especially in the following topics: model, critical multicultural education, multicultural competency, responsive teaching, teacher candidate, preservice teacher, ethnic minority student, self-efficacy, diverse student, multicultural content, responsive pedagogy, critique, intercultural education, peace, dan personality. The implications of these findings are for the development and improvement of future multicultural education research and publications.